Optimizing Physical Adaptation Sprint Performance Trough Resistance Training in Youth Atlhetes: A Literature Riview - Drastiana Siwi Maheswari; Hijrah Maulidiah Afifah; Ramlan Sembada (Universitas Negeri Semarang, 2025)
Long Term Athlete Development (LTAD) program emphasizes trhe importance of continous and structurud physiscal development of athletes according to the stage of growth and maturity of the individual. Resistance training is one of the main components in supporting athletic sprint performance, especially in youth athletes. This study aims to review the effect of resistance training on physiscal adaptation that support improved sprint performance through the litterature riview method. A total 10 relevant scientific articles published between 2014-2024 were thematically analyzed to identify the impact of resistance training ion physical performance variables. The result of this study show that systematically planned resistance training can improve lower extremity muscle strength, sprint acceleration, speed, explosive power, and movement coordination. Methode such as Velocity-Based Training (VBRT), the use of Resistance Wearalbles, the combination od Squats with Sled Towing and Speed-Based Load Setting proved effective in improving sprint performance. Another advantage of resistance training is that it can reduce the risk of injury and support the long-term health of youth athletes. This study emphasizes the importance of including resistance training in LTAD programs for sprint athletes to achive peak performance and prevent the negative effcts of overtraining. Therefore , incorporating resistance training into youth sprint program sis essential for optimizing performance outcomes. Future studies should explore individualized resistance training protocols tailord to differant stages of athlete development.